Public Image and Private Life of Ai Hoshino in Oshi no Ko: A Dramaturgical Analysis - Faishal Seananda; Parastuti Parastuti; Rusmiyati Rusmiyati; Didik Nurhadi (Chi e Journal of Japanese Learning and Teaching, 2026)
The idol phenomenon is a prominent aspect of modern popular culture, in which individuals are expected to present an idealized image that conforms to social expectations. In this context, impression management plays a central role in shaping an idol’s public identity. This phenomenon is also represented in popular media, including the anime Oshi no Ko. This study examines the construction of public image and private life in the character Ai Hoshino through her performances in the front stage and backstage. Using a qualitative descriptive approach and non-participant observation, the data were collected from dialogues, monologues, and relevant scenes in the anime. The analysis draws on Erving Goffman’s dramaturgical theory, particularly the concepts of performance, front stage, and backstage. The findings show that the boundary between public image and private life is not simply blurred but actively constructed through complex social mechanisms. Through face-work, sign vehicles, and team performance, Ai Hoshino consistently maintains her public image as an idol. Overall, Oshi no Ko represents dramaturgical practices in Japanese idol culture through the deliberate construction and management of image.